2000
DOI: 10.1038/sj.ejhg.5200543
|View full text |Cite
|
Sign up to set email alerts
|

CYP21 and CYP21P variability in steroid 21-hydroxylase deficiency patients and in the general population in the Netherlands

Abstract: Steroid 21-hydroxylase deficiency is caused by defectiveness of the CYP21 gene. Such defects have presumably originated from interactions with the nearby CYP21P pseudogene during evolution. We studied these mechanisms by comparing the genetic variability of CYP21, CYP21P, and CYP21P/CYP21 hybrids (resulting from large-scale rearrangements) at eight mutation sites in a group of Dutch steroid 21-hydroxylase deficiency patients, their family members, and controls. The most common CYP21 defect in patients with sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 39 publications
(87 reference statements)
1
26
0
2
Order By: Relevance
“…This finding further confirms that allele PCR dropout in previous PCR analyses was in fact caused by the presence of the 5' end region of the CYP21P sequence, which is consistent with our previous suggestion (Lee et al 2000). Since an antisense primer anchored at nt 707-714 of CYP21 has been used in most primary PCR amplifications (Tajima et al 1993;Day et al 1996;Koppens et al 2000) to eliminate CYP21P contamination, it may have led to PCR dropout in detecting CYP21 mutations of IVS2-12A/C>G combined with707-714delGAGAC-TAC and the chimeric CYP21P/CYP21.…”
Section: Properties Of the Chimeric Cyp21p/cyp21 Genesupporting
confidence: 91%
See 4 more Smart Citations
“…This finding further confirms that allele PCR dropout in previous PCR analyses was in fact caused by the presence of the 5' end region of the CYP21P sequence, which is consistent with our previous suggestion (Lee et al 2000). Since an antisense primer anchored at nt 707-714 of CYP21 has been used in most primary PCR amplifications (Tajima et al 1993;Day et al 1996;Koppens et al 2000) to eliminate CYP21P contamination, it may have led to PCR dropout in detecting CYP21 mutations of IVS2-12A/C>G combined with707-714delGAGAC-TAC and the chimeric CYP21P/CYP21.…”
Section: Properties Of the Chimeric Cyp21p/cyp21 Genesupporting
confidence: 91%
“…There have been various studies (White et al 1988;Sinnott et al 1990;Levo and Partanen 1997;Koppens et al 2000) indicating hybrid genes with the 30-kb deletion between CYP21P and CYP21 genes in Caucasians. Several studies (Lee et al 2002;Lee et al 2003a) have shown that there are three distinct chimeric CYP21P/CYP21s in the CYP21 gene in the ethnic Chinese population in Taiwan.…”
Section: Types Of Chimeric Cyp21p/cyp21mentioning
confidence: 99%
See 3 more Smart Citations